Understanding research - Neuman, William Lawrence , 1950- (Boston, Massachusetts : Pearson/Prentice Hall, 2012)
Understanding Research is an accessible and visually-appealing introduction to research. Whether students become producers or consumers of research, this text shows them that the subject is both interesting and highly relevant for their lives and professional work
Why do research? -- 2. Planning a study -- 3. Becoming an ethical researcher -- 4. Sampling: how to select a few to represent the many -- 5. Measuring social life -- 6. The survey: asking people questions -- 7. The experiment -- 8. Research with nonreactive measures -- 9. Making sence of the numbers -- 10. Observing people in natural settings -- 11. Looking at the past and across cultures -- 12. Writing a research report
Includes bibliographical references and index
Keywords: Social sciences -- Methodology; Social sciences -- Research; Sociology -- Methodology; Sociology -- Research